Study to estimate the prevalence of risk factors of chronic disease among a fishing community in Tamil Nadu - Seenivasan, P.; Caroline Priya, K.; Siddharth, Raghul; Devanand, S.; Siva Surya, A.; Sarath, G.; Kavin Chander, M.; Sivasharan, K.; Raj Kumar, H. (International Journal Of Community Medicine And Public Health, 2018)
Background: Studies have shown that fishermen have a higher mortality from cardiovascular disease, cancer and accident. Despite existing knowledge regarding the high morbidity and mortality rates associated with fishing, there has been little research on the effect of working conditions on the health of fishermen, especially in the developing world. To estimate the prevalence of risk factors of chronic disease among the fishing community in Pulicat village and to find the association among various risk factors. Methods: This cross-sectional study was carried out from March 2016 to September 2016, among the residents of Pulicat village, a fishing community to the north of Chennai. The core items in of the WHO steps instrument were used, the questionnaire also included data on demographics and socio-economic variables. Results: Fruit consumption was low among the study population only 15.11% and 12.44% consumed fruits and vegetables daily, 25% of the population were involved in vigorous activity daily, 4.44% of the population was smokers, 18.67% of them consumed alcohol, 31.11% of them were hypertensive, 12.81% were diabetic. BMI calculations showed that 37.33% were above the normal range and 52.44% had waist circumference above the normal range. Conclusions: Health promotion and education initiatives should be conducted in the fishing community to increase the awareness of the risk for developing chronic diseases which may permanently incapacitate them and force them to quit their profession. They should be encouraged to avoid alcohol, smoke less, eat more fruits and vegetables especially at sea, increase physical activity, and monitor regularly their weight, abdominal circumference and blood pressure.